PAWAI OGOH-OGOH DAN NYEPI DI PULAU SERIBU MASJID: PENGUATAN IDENTITAS AGAMA DI RUANG PUBLIK - Erni Budiwanti (Harmoni, 2018)
The Indonesian government recognizes six official religions: Islam, Christianity, Catholicism, Hinduism, Buddhism, and Confucianism, manifested in the way the government sets up public holidays based on important religious events. It also guarantees freedom of religious expression for different believers to behave according to what they believe, as stipulated in the article 29 of the 1945 Constitution of the Republic of Indonesia. Government’s recognition upon three types of New Year event: Hijriya for Muslims, Saka for Hindu-Balinese, and Imlek for Chinese as annual holiday marks further the notion of religious pluralism in Indonesia. This paper focuses on the Ogoh-Ogoh ritual as an integral part of Nyepi (the day of seclusion) which since 1983 has been legalized by the Presidential Decree Number 3 as national holiday. The Hindu communities, living in Bali and Lombok, celebrate this annual ritual event as part of exhibiting their religious commitment andeffort of maintaining identity. The main issues elaborated here include firstly, on the dynamics of the Hindu-Balinese minority of Lombok in preserving their religious tradition amidst the majority of the Sasak Muslims. Secondly, the Sasak Muslims’ response toward the Ogoh-Ogoh display which has, to some extent, taken some of the most strategic public space of Mataram-capital city of NTB province, and influenced the surrounding social atmosphere. Thirdly, the way the minority Muslims in Bali deal with regional policy and regulation regarding to Nyepi. This discussion discloses the nature of relationship between Hindu-Balinese and Muslims in Bali, and between the Sasak Muslims and Hindu-Balinese in Lombok. It seems that a mutually partial tolerance between these groups are slightly developed by means of the Ogoh-Ogoh and Nyepi.